Evaluation of supply chain management: a case study on Kallol Enterprise Limited of Kallol Group of Companies - Islam, Mohammad Zohirul (BRAC University, 2015)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2014.